EFFECT OF DIFFERENT CONCENTRATION OF PAPAIN ENZYME TOWARDTOTAL AMINO ACID OF EEL (Monopterus albus) PROTEIN HYDROLYSATE - Ayu Agustina; Rahman Karnila; Mirna Ilza (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACT This research was aimed to determine the proximate chemical content of eel (Monopterus albus) meat, obtain the eel protein hydrolysate from different concentration of papain enzymes, and determine the total amino acid of eel protein hydrolysate. The method used was an experimental method with a Completely Randomized Design (CRD). The treatments used was various concentrations of papain enzymes P1(3%), P2 (5%), P3(7%). Parameters observed were proximate analysis (moisture, ash, protein, fat, and carbohydrate content) of eel protein hydrolysate, total amino acid analysis and yield. The results showed that the proximate content of eel meat was 81.28% moisture content, 1.76% ash content, 14.54% protein content, 1.28% fat content, and 1.14% carbohydrate (by difference). Total amino acids analysis of P1, P2, and P3 treatments were 14.03%, 14.86%, and 15.66%, respectively.The different concentration of papain enzymes had a very significant effect on yield, whereas the yields of P1, P2, and P3 treatments were 33.05%, 35.25%, and 37.15%, respectively. Keywords: Fish protein hydrolysate, eel, papain enzyme